THE ROLE OF INSTITUTIONAL SHAREHOLDERS IN INDONESIA'S MANUFACTURING COMPANY - Eka Septa Kurniawan; Arasy Rachman; Agus Sukoco; Agus Dwi Sasono; Wahyu Mulyo Utomo (AIBPM Publisher, 2018)
The purpose, This study aims to analyze the effect of Return On Assets, Debt To Equity Ratio, Dividend Payout Ratio to the Institutional Ownership in Manufacturing Companies listed in Indonesia Stock Exchange (IDX) period 2012-2014 Method, The Research was conducted at Manufacturing companies listed on Indonesia Stock Exchange period 2012 - 2014. The data source came from 18 Manufacturing companies with purposive sampling technique. SPSS version 20 software analysis technique was employed using t test and F test on multiple linear regression to find the effect of Return on Asset, Debt to equity ratio, Debt payment ratio and institutional ownership. Result, The results of the study found that the change in value on the variable Return On Asset, Debt to Equity Ratio, Dividend Payout Ratio did not have a significant effect on the ownership of the manufacturing company in Indonesia The findings, The findings of the research are that in manufacturing companies in Indonesia, the value of institutional shares owned by the company is not influenced by changes that occur in the ability to pay the debt, the ability to pay dividends and return on assets. Keywords: Institutional, shareholder, Debt to Equity Ratio, Dividend Payout Ratio